2021
DOI: 10.3389/fcell.2021.706171
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Alloantibody Responses

Abstract: The control of alloimmunity is essential to the success of organ transplantation. Upon alloantigen encounter, naïve alloreactive T cells not only differentiate into effector cells that can reject the graft, but also into T follicular helper (Tfh) cells that promote the differentiation of alloreactive B cells that produce donor-specific antibodies (DSA). B cells can exacerbate the rejection process through antibody effector functions and/or B cell antigen-presenting functions. These responses can be limited by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…CD24 appears to be one of the major actors in immune tolerance. It is a cell-surface protein marking B-reg cells, a subset of B cells that suppress immune reactions [38], as was already found in organ transplantation [38,39]. Since gestation can be defined as a semi-allograft, it would be desirable to identify whether B-reg-cell-mediated immune modulation is involved in a successful pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…CD24 appears to be one of the major actors in immune tolerance. It is a cell-surface protein marking B-reg cells, a subset of B cells that suppress immune reactions [38], as was already found in organ transplantation [38,39]. Since gestation can be defined as a semi-allograft, it would be desirable to identify whether B-reg-cell-mediated immune modulation is involved in a successful pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…18,36 Multiple studies have found that humoral immunity to foreign MHC involves GC reaction and FO T helper cell formation. 2 Circulating T helper cells have been identified as a marker of ongoing alloimmunity and graft rejection. 2,37,38 Our findings are not incongruent with this work but rather demonstrate that the MZ B cells, not FO B cells, are the major reservoir from which the GC B cells are derived.…”
Section: Discussionmentioning
confidence: 99%
“…2 Circulating T helper cells have been identified as a marker of ongoing alloimmunity and graft rejection. 2,37,38 Our findings are not incongruent with this work but rather demonstrate that the MZ B cells, not FO B cells, are the major reservoir from which the GC B cells are derived. It is not clear whether the selective activation of MZ B cells versus FO B cells is because of differences in the threshold for activation (eg, signaling through inflammatory mediators) or the B cell receptor specificity for allogeneic antigens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tfr inhibit through production of IL-10 and PD1 ( 244 ). Other regulatory cells, such as tTreg, regulatory B cells can inhibit alloantibody production ( 245 ). In a murine model, while Tfh cells are required for production of alloantibody, absence of Tfr worsenes alloantibody production and rejection ( 246 ).…”
Section: Activated/memory Tregmentioning
confidence: 99%